Second Primary Lung Adenocarcinoma After Intensity-Modulated Radiotherapy for Nasopharyngeal Carcinoma - Xue, Fen; Niu, Xiaoshuang; Hu, Chaosu; He, Xiayun (Frontiers in Oncology, 2022)
Objective: The improvement of the efficacy of intensity modulated radiotherapy (IMRT) for nasopharyngeal cancer (NPC) has prolonged the survival of patients, and the incidence of the second tumor has gradually increased. Among them, second primary lung adenocarcinoma (SPLAC) attributes the highest incidence. This study aimed to determine the long-term risk of SPLAC in NPC patients after IMRT. Methods: From May 2005 to May 2018, a total of 1102 non-metastatic NPC patients who received IMRT in our hospital were enrolled, and the incidence and efficacy of SPLAC were followed up in the long term. Results: Over a median follow-up period of 66 months, a total of 22 cases of SPLAC were observed, with an incidence of 2.0%. The 1-, 2-, 3-, 4-, and 5-year cumulative risks of SPLAC were 0.4%, 0.7%, 0.8%, 1.1%, and 1.7%, respectively. During follow-up, 90.9% (20/22) of the SPLAC detected was in early stage, and the recurrence rate of surgery alone was 5.3% (1/19). Conclusion: In NPC patients, the proportion of SPLAC after IMRT was similar to that of the normal population, and most of them were found in early stage during follow-up, with good surgical efficacy.